History of education among the Cambodian Muslims - Mohamad Zain Musa (Penerbit UKM, 2011)
The members of the Cambodian Muslims consits of two main groups, the Chams and the Malays. Nevertheless there are some of Arab, Indian, Pakistanis and Afghan origins. After Cambodia independence they are officially known as Khmer Islam (Muslim Khmer). Since their arrivals, the Chams and the Malays were well accepted by the Khmer communities at all levels. The Khmer Islam can freely choose any village to reside, any job to do for their living or they may work as a government officer or civil servants or else they may join the armed forces. Among them there are some who had been appointed to the highest position in the royal government’s administration hierachy such as governors and ministers. Islam as their religion can freely be practiced together with their traditional Islamic education system for their children. To date this freedom can still be widely seen. This paper discusses the long and winding history of the Cambodian Muslim education; how they keep up with changes and development brought about in the country where the majority of its population is Buddhist. This paper tries to trace the history of how Islam is taught to the members of the community. How the dynamism of Imam Musa’s ideals and visions together with the Muslim brothers from the Malay archipelago have established a strong system which in their view has helped to maintain the balance in their daily life to be a good citizen and to preserve their own identity as Muslim.